Strength training reduces injury rate in elite young soccer players during one season - Zouita, S.; Zouita, A. B. M.; Kebsi, W.; Dupont, G.; Ben Abderrahman, A.; Ben Salah, F. Z.; Zouhal, H. (The Journal of Strength and Conditioning Research, 2016)
The purpose of this study was to examine the effect of strength training on physical fitness parameters and injuries occurrence in young elite soccer players. Fifty-two elite young soccer players (13-14 years) were divided on a randomized order into experimental group (EG, n = 26) and control group (CG, n = 26). For EG, 2 to 3 sessions of strength training (90 minutes) were introduced weekly in their training program for 12 weeks (4 × 3 weeks separated by 1-week recovery). Sprint tests (10-20-30 m), T-test time, and jumping tests were measured at the start (T0), at the middle (T1), and at the end of the experiment period (T2). The injury rate was recorded by the medical and fitness training staff throughout the soccer season. Compared to CG, EG performed significantly better in sprint running and T-test time at T2 (p < 0.01). Similarly, the improvement amount for jumping tests was significantly greater (p = 0.05) in EG than in CG. A total of 17 injuries were recorded over the soccer season. The rate was higher in CG (13 injuries) than in training group (4 injuries). This study showed that strength training accurately and efficiently scheduled in youth soccer players, induced performance improvement, and reduced the rate of injuries.